2023
DOI: 10.3390/jof9030310
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis and Characterization of Cupric Oxide Loaded 2D Structure Graphitic Carbon Nitride (g-C3N4) Nanocomposite: In Vitro Anti-Bacterial and Fungal Interaction Studies

Abstract: The active and inexpensive catalyst cupric oxide (CuO) loaded foliar fertilizer of graphitic carbon nitride (g-C3N4) is investigated for biological applications due to its low cost and easy synthesis. The synthesized CuO NPs, bulk g-C3N4, exfoliated g-C3N4, and different weight percentages of 30 wt%, 40 wt%, 50 wt%, 60 wt%, and 70 wt% CuO-loaded g-C3N4 are characterized using different analytical techniques, including powder X-ray diffraction, scanning electron microscopy, energy dispersive X-ray analysis, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Nanomaterials have been used in many applications, such as catalysis, water splitting, supercapacitors, biology, agriculture, pharmaceuticals, etc. ,, In benchmark studies, the two main factors that dictate nanomaterial behavior are surface effects and quantum effects. These effects enhance the physiochemical properties such as catalytic, mechanical, thermal magnetic, and optical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanomaterials have been used in many applications, such as catalysis, water splitting, supercapacitors, biology, agriculture, pharmaceuticals, etc. ,, In benchmark studies, the two main factors that dictate nanomaterial behavior are surface effects and quantum effects. These effects enhance the physiochemical properties such as catalytic, mechanical, thermal magnetic, and optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, various morphologies of copper-based metal oxide catalysts such as spheres, rods, belts, rolling pins, octahedrons, and throne, have shown high activity in heterogeneous catalysis due to their better physicochemical properties. Despite being widely studied, CuO nanocatalysts remain unexplored in catalysis, particularly with respect to its various shapes. , Research has shown that shape effects play a crucial role in organic reactions, with surface energy, surface area, structures, and active sites being key features. For example, nanocubes have been found to exhibit a higher rate of reduction in the hydrogenation reaction of the nitro compounds by silver nanoparticles due to their different facets and higher adsorption sites.…”
Section: Introductionmentioning
confidence: 99%